Religion and the Conceptual Boundary in Central and Eastern Europe Encounters of Faiths - Bremer, T.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This volume concentrates on the 'conceptual boundary' through Europe which is determined by Western and Eastern Christianity. The chapters show that the boundary has never been a stable and defined division, but that it was also subject to change and development and a place of encounter and exchange between religions and cultures.
Keywords: European Union; Europe—Politics and government; Religion and sociology; World politics; Europe—History.; Political science; European Union Politics; European Politics; Social Aspects of Religion; Political History; European History; Political Science